A rare cause of obscure gastrointestinal bleeding: Chronic enteropathy associated with SLCO2A1 mutation in a case from India - Shivani Chopra; Vikramaditya Rawat; Meghraj Ingle; Saiprasad Lad; Mit Shah; Deepak Sasikumar; Vinay Borkar; Yatin Lunagariya; Somraj Patil (Society of Gastrointestinal Intervention, 2024)
A 13-year-old boy presented with an 8-year history of repeated episodes of anemia. Laboratory investigations confirmed iron deficiency anemia due to occult blood loss from the gastrointestinal tract. Despite undergoing esophagogastroduodenoscopy, colonoscopy, and push enteroscopy, no abnormalities were detected. Subsequent computed tomography enterography also yielded normal results. However, a capsule endoscopy revealed multiple superficial ulcers in the jejunum and proximal ileum. Initially, the patient was treated for Crohn's disease using various therapeutic approaches, all of which were unsuccessful. Further investigation led to a positive diagnosis for a rare condition known as chronic enteropathy associated with SLCO2A1 mutation (CEAS), marking the first reported case in India.